2016
DOI: 10.1007/s10461-016-1629-x
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Home-Based Versus Outreach Event-Based Community HIV Testing in Ugandan Fisherfolk Communities

Abstract: We compared two community-based HIV testing models among fisherfolk in Lake Victoria, Uganda. From May to July 2015, 1,364 fisherfolk residents of one island were offered (and 822 received) home-based testing, and 344 fisherfolk on another island were offered testing during 8 community mobilization events (outreach event-based testing). Of 207 home-based testing clients identified as HIV-positive (15% of residents), 82 were newly diagnosed, of whom 31 (38%) linked to care within 3 months. Of 41 who screened po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
50
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(51 citation statements)
references
References 52 publications
(40 reference statements)
1
50
0
Order By: Relevance
“…We also did not vary our input costs in the uncertainty analysis, and the costs of the novel testing modalities that have not been implemented at scale in the public sector (in particular self-test distribution) are currently based on assumptions regarding staff time, linkage and the number of tests that can be performed per day. Rates of linkage to ART after diagnosis are difficult to determine in the context of community-based models of HIV testing, which generally suffer from lower rates of linkage than facility-based testing 18,[49][50][51] . In our uncertainty analyses, we found that in most community-based testing scenarios the cost per life year saved declined substantially as the rate of linkage to ART increased (Table S3.11), and it is therefore important to quantify linkage rates more precisely.…”
Section: Discussionmentioning
confidence: 99%
“…We also did not vary our input costs in the uncertainty analysis, and the costs of the novel testing modalities that have not been implemented at scale in the public sector (in particular self-test distribution) are currently based on assumptions regarding staff time, linkage and the number of tests that can be performed per day. Rates of linkage to ART after diagnosis are difficult to determine in the context of community-based models of HIV testing, which generally suffer from lower rates of linkage than facility-based testing 18,[49][50][51] . In our uncertainty analyses, we found that in most community-based testing scenarios the cost per life year saved declined substantially as the rate of linkage to ART increased (Table S3.11), and it is therefore important to quantify linkage rates more precisely.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, several of the rural/remote study facilities serve highly mobile patient populations such as fisherfolk living on Lake Victoria and migratory cattle farmers. HIV prevalence among Ugandan fisherfolk is high relative to the general population (15-40%) [ 29 , 30 ] and fisherfolk are known to have poor linkage (e.g., 38% within 3 months of outreach event-based testing) [ 9 ]. Barriers to care in this population include limited healthcare access, quality of care, and social support, high mobility, competing work demands during clinic hours, and stigma [ 9 ], and community-based testing programs appear promising to improve linkage in these communities [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…HIV prevalence among Ugandan fisherfolk is high relative to the general population (15-40%) [ 29 , 30 ] and fisherfolk are known to have poor linkage (e.g., 38% within 3 months of outreach event-based testing) [ 9 ]. Barriers to care in this population include limited healthcare access, quality of care, and social support, high mobility, competing work demands during clinic hours, and stigma [ 9 ], and community-based testing programs appear promising to improve linkage in these communities [ 9 ]. Interventions to improve linkage and retention may need to provide additional support and more patient-centered models of care to women, adolescents, and patients in rural and highly transitory communities.…”
Section: Discussionmentioning
confidence: 99%
“…Despite this possibility, our study team observed the opposite. Individuals may be less likely to link to HIV clinical care following home-based testing [ 20 , 47 ], as newly diagnosed individuals cannot easily be personally escorted to HIV clinic for immediate linkage as can be achieved during clinic-based testing. Follow-up data collection was beyond the scope of this pilot study; therefore, we were unable to evaluate linkage to care after home-based testing based on these data.…”
Section: Discussionmentioning
confidence: 99%
“…Home-based HIV testing has been effective in many resource limited settings in sub-Saharan Africa [ 8 20 ], but may not be a successful testing strategy in a refugee settlement. Many refugees have endured violent conflict and/or sexual violence [ 5 , 21 ], and thus may be less willing to accept strangers into their homes.…”
Section: Introductionmentioning
confidence: 99%